Construction project scheduling under workspace interference - Tao, Sha; Wu, Changzhi; Hu, Shaolong; Xu, Feng (Computer-aided civil and infrastructure engineering, 2020)
Workspace interference in construction sites usually leads to work inefficiency, rework, and risk to the workforce. In this paper, we present a study on controlling and mitigating workspace interference in construction project scheduling. In particular, we consider two types of workspace interference: unacceptable workspace interference (USI) and acceptable workspace interference (ASI). During the scheduling process, if two activities cause USI, they must be scheduled for non‐overlapping execution periods. If the two activities that cause ASI are executed concurrently, it will lead to decrease in productivity. We first establish a mathematical model for construction project scheduling subject to these two types of workspace interference. This established model is a mixed‐integer, multiobjective optimization problem. Then, a two‐stage metaheuristic algorithm is developed to solve the problem. Two construction scenarios are selected to illustrate the effectiveness of the proposed method. By comparing with traditional forward scheduling method, the two‐stage metaheuristic algorithm can achieve solutions with, on average, shorter project makespan, less total cost as well as milder resource usage variation in execution.